Siglec receptors impact mammalian lifespan by modulating oxidative stress - Schwarz, Flavio; Pearce, Oliver MT; Wang, Xiaoxia; Samraj, Annie N; Läubli, Heinz; Garcia, Javier O; Lin, Hongqiao; Fu, Xiaoming; Garcia-Bingman, Andrea; Secrest, Patrick; Romanoski, Casey E; Heyser, Charles; et al. (eLife, 2015)
Aging is a multifactorial process that includes the lifelong accumulation of molecular damage, leading to age-related frailty, disability and disease, and eventually death. In this study, we report evidence of a significant correlation between the number of genes encoding the immunomodulatory CD33-related sialic acid-binding immunoglobulin-like receptors (CD33rSiglecs) and maximum lifespan in mammals. In keeping with this, we show that mice lacking Siglec-E, the main member of the CD33rSiglec family, exhibit reduced survival. Removal of Siglec-E causes the development of exaggerated signs of aging at the molecular, structural, and cognitive level. We found that accelerated aging was related both to an unbalanced ROS metabolism, and to a secondary impairment in detoxification of reactive molecules, ultimately leading to increased damage to cellular DNA, proteins, and lipids. Taken together, our data suggest that CD33rSiglecs co-evolved in mammals to achieve a better management of oxidative stress during inflammation, which in turn reduces molecular damage and extends lifespan.
Keywords: inflammation; reactive oxygen species; aging; Siglec